Integrating metabolite and transcriptome analysis revealed the different mechanisms of characteristic compound biosynthesis and transcriptional regulation in tea flowers - Tang, Dingkun; Shen, Yihua; Li, Fangdong; Yue, Rui; Duan, Jianwei; Ye, Zhili; Lin, Ying; Zhou, Wei; Yang, Yilin; Chen, Lixiao; Wang, Hongyan; Zhao, Jian; et al. (Frontiers in Plant Science, 2022)
Tea flowers contained abundant second metabolites, as well as tea leaves, and was a big potential resource for extraction of bioactive compounds or preparation of functional foods. However, little is known about the biosynthesis and transcriptional regulation mechanisms of those metabolites in tea flowers, such as terpenoid, flavonol, catechins, caffeine, and theanine. This study integrated target and nontarget metabolism analyses finely exploring the metabolic feature of tea flowers. Tea flowers accumulated more abundant terpenoid compounds than young leaves. Transcriptome data of developing flowers and leaves showed that higher expression level of later genes of terpenoid biosynthesis pathway, such as Terpene synthases gene family, in tea flowers is the reason of more abundant terpenoid compounds than tea leaves. Differently, even though flavonol and catechins profiling in tea flowers and leaves is similar, the gene family members of flavonoid biosynthesis were selectively expressed by tea flowers and tea leaves. We also found the different regulatory mechanism of flavonol biosynthesis in tea flowers and leaves. Otherwise, similar regulatory mechanism of catechins biosynthesis in tea flowers and leaves. This study not only provides a global vision of metabolism in tea flowers, but also uncovered the different mechanism of biosynthesis and transcriptional regulation of those important compounds.